Investigation reform in Russia in the second half of the 19th century - Nikolay Yu. Andreev, Larisa L. Solovyova, Roman R. Palekha, Valery P. Kanishchev, (Opción, 2019)
The research objective is to study the reform of court investigators' institutions in the central regions of Russia in the second half of the 19th century. The methodological basis of the study is the dialectical method universal in legal science. As a result, most of the shortcomings occurred in the process of applying the rules of regulating the competence of the police and judicial investigators during the preliminary investigation. In conclusion, the institute of judicial investigators itself underwent fundamental changes, and since the late 1880s, the era of counter-reforms began.